Sedimentary records and chronology of the late Pleistocene overbank flooding in the Yellow River source area, NE Tibetan Plateau - Zhu, Yan; Wang, Haoyu; Zhang, Yuzhu; Huang, Chun Chang; Zha, Xiaochun; Qiu, Haijun; Jia, Ya-na; Xiao, Qili; Chen, Dou; Lin, Xu; Liu, Tao (Frontiers in Earth Science, 2022)
Abstract: Paleohydrological investigations were carried out in the Yellow River source area on the northeast (NE) Tibetan Plateau. During our fieldwork investigations, two units of overbank flood deposits (OFD) were found in the Maqu-Kesheng reach. These OFD units were studied using a multi-index approach, including magnetic susceptibility, hygroscopic water, grain size distribution and micro-morphological features. It can be inferred that they have recorded two episodes of overbank flooding of the Yellow River. Using the optically stimulated luminescence (OSL) and AMS 14C dating techniques, the first episode was dated to 34680±1880-29000±1790 a and correlated with the late Marine isotope stage (MIS) 3a with a warm and wet climate. The second episode occurred at 16500±1250-14000±1280 a, which is coincided with the Bølling-Allerød warm stage during the last deglaciation, a period of coexisting global warming and rapidly shrinking ice sheets. At these two periods, the water was mainly derived from the accelerated melting of mountain glaciers surrounding the basin and/or the large-scale precipitation, which led to the overbank flooding events. At the same time, the related overbank flood deposits were interbedded within glacial outwash/flashflood deposits in the valley bottom of the Yellow River, which intensified the valley aggradation. These results are of great significance in enriching the paleoflood records in the Yellow River source area, recognizing the effect of river system on the development of valley landform, as well as understanding the hydro-climatic response of the Tibetan Plateau to global climate warming occurring presently.